Development and Validation of a Nomogram for Predicting Mortality in Patients with Atrial Fibrillation and Acute Coronary Syndrome Who Underwent Percutaneous Coronary Intervention in a Chinese Multicenter Cohort - Can Hua; Haitao Tian; Yubin Wang; Jianyong Zheng; Pengfei Liu; Boyang Zhang; Nannan Wang; Haihong Tang; Feng Wang; Xiufeng Xie; Haifeng Yuan; Tianchang Li (Applied Bionics and Biomechanics)
Background. This study is aimed at to establish an effective prognostic nomogram for patients with atrial fibrillation (AF) and acute coronary syndrome (ACS) underwent percutaneous coronary intervention (PCI). Methods. The nomogram was based on a retrospective study of 977 patients with AF and ACS who underwent PCI who were admitted to any of the 11 tertiary hospitals in the Beijing area between 2009 and 2015. The predictive accuracy and discriminative ability of the nomogram were determined by a concordance index (C-index) and calibration curve and were compared using current risk scores such as GRACE, CRUSADE, CHA2DS2-VASc, and HAS-BLED. The results were validated using bootstrap resampling and a retrospective cohort study of 409 patients enrolled in Fuwai Hospital at the same institution. Results. Independent factors derived from multivariable analysis of the primary cohort to predict all-cause mortality were age, pattern of ACS, red blood cell distribution width, N-terminal proBNP, and serum creatinine, all of which were assembled into the nomogram. The calibration curve for the probability of recurrence showed that the nomogram-based predictions were in good agreement with actual observations. The C-index of the nomogram for predicting mortality was 0.764 (95% CI, 0.718-0.810), which was statistically higher than the C-index values for the current risk scores (from 0.573 to 0.681). In the validation cohort, the C-index of the nomogram for predicting all-cause death was 0.706 (95% CI 0.601-0.811), with no significant differences compared with GRACE and CRUSADE, but better than that of CHA2DS2-VASc and HAS-BLED. Conclusions. The nomogram has good prognostic prediction for patients with AF and ACS who underwent PCI.